Multi-Objective Dynamic Resource Scheduling Model for Allocating User Tasks in the Cloud Computing - et. al., G.B. Hima Bindu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing is the efficient distributed platform which manages all types of resources in the virtual manner. The major functionality of the cloud computing is to schedule the user tasks to the virtual machines. Many algorithms are proposed by the researchers to address the scheduling in cloud. Though there is some research gap need to be focused in the cloud scheduling. Minimizing the cost, makespan and deadline violations are difficult when large volume of tasks are assigned to the cloud. The multi-objective mechanisms are needed to address the two more objectives in the cloud scheduling model. This paper proposed the multi-objective algorithm based on the non-dominated method and crowding distance method. The proposed method computes the quality of service for the virtual machines before allocating to tasks to fulfil the requirements of the users. The performance of the proposed multi-objective model is evaluated based on the makespan, deadline violations and cost. The results prove the efficiency of the multi –objective model.